Two new species of the genus Teulisna Walker (Lepidoptera, Erebidae, Arctiinae, Lithosiini) from Myanmar and Nepal - Huang, Si-Yao; Volynkin, Anton V.; Müller, Günter C. (Zootaxa, 2024)
Two new species of the genus Teulisna Walker, 1862 are described: T. kishidai Huang, Volynkin & Müller sp. n. from Mount Victoria, West Myanmar, and T. hreblayi Volynkin & Huang sp. n. from East Nepal. Both species are compared with members of the T. pallida (Moore, 1878) species-group. Adults and genitalia of both sexes are illustrated.